DIVERSIFICATION OF INVESTMENT PROJECTS FINANCING SOURCES ON THE BASIS OF PUBLIC-PRIVATE PARTNERSHIP MECHANISM - M. Arzumanyan (Вестник университета, 2017)
This article presents the specifics of financing investment projects on the basis of public-private partnership in the current realities of the economy. Analysis of the current international practice of designated projects allows identifying key aspects in the formation of sources of their financing. In this article the author proves the need to take into account the specific factors of each of the stages of the project life cycle in the implementation of investment attraction, which allows project companies to gain access to new sources of liquidity.